زیرەكیی زمانیی لاى بێژەرى تەلەفزیۆنى - محمد, عبدالصمد احمد (Sulaimani Journal for Humanities, 2018)
This study entitled Linguistics Intelligence of TV Presenters is composed of four main sections. The first section touches upon the problem of the study, its aim, its value, its scope, as well as a bunch of key related notions and terms. Section Two is the theoretical background of the study in which a number of variables of linguistic intelligence and TV presenting are discussed. Section Three covers the research design, the population and the sample, validity and stability of the methods employed in the study. It is worthy to note that the sample of the research represents a number of presenters working at Kurdish space channels like Kurdsat , NRT , Payam ,KNN. The number of the participants was 56 TV presenters (male and female). Finally, in Section Four , which is the concluding section, the results and their analysis are discussed. The study concludes that linguistic intelligence of Kurdsih TV presents is at a very high level. Comparing the male participants to the females, the results show that the males are more linguistically intelligent. In the conclusion of this section, a number of recommendations are suggestions are made by the researcher.